Silver as a Constraint for a Large-Scale Development of Solar Photovoltaics? Scenario-Making to the Year 2050 Supported by Expert Engagement and Global Sensitivity Analysis - Lo Piano, Samuele; Saltelli, Andrea; van der Sluijs, Jeroen P. (Frontiers in Energy Research, 2019)
In this study we assess whether availability of silver could constrain a large-scale deployment of solar photovoltaics (PV). While silver-paste use in photovoltaics cell metallization is becoming more efficient, solar photovoltaics power capacity installation is growing at an exponential pace. Along photovoltaics, silver is also employed in an array of industrial and non-industrial applications. The trends of these uses are examined up to the year 2050. The technical coefficients for the expansion in photovoltaics power capacity and contraction in silver paste use have been assessed through an expert-consultation process. The trend of use in the non-PV sectors has been estimated through an ARIMA (auto-regressive integrated moving average) model. The yearly and cumulative silver demand are evaluated against the technological potential for increasing silver mining and the estimates of its global natural availability, respectively. The model implemented is tested with a quasi-random Monte Carlo variance-based global sensitivity analysis. The result of our inquiry is that silver may not represent a constraint for a very-large-scale deployment of photovoltaics (up to tens TW in installed power capacity) provided the present decreasing trend in the use of silver paste in the photovoltaics sector continues at an adequate pace. Silver use in non-photovoltaic sectors plays also a tangible influence on potential constraints. In terms of natural constraints, most of the uncertainty is dependent on the actual estimates of silver natural budget.